Uma poética em performance arte: as relações afetivas atravessadas pela cibercultura - Rodrigues, Marcella Nunes (2020)
The thesis presents the master’s degree research developed in the Postgraduate Program in Visual Arts, Arts and Letters Center of the Federal University of Santa Maria (UFSM) in Visual Poetics in Contemporary Art. The investigation is inserted in the line of Art and Culture. The study’s objective consisted in the creation of performances that discuss the entry of technology in relationships, specifically, in the heterosexual affective relations. The preference for the Performatic Art artistic language unfolded because it’s a phenomenon that encompasses art, body, and communication, being characterized by the immersion in overt and latent social issues. The theorists Goldberg (2006) and Taylor (2011) supported and consolidated the performatic actions in their theoretical-practical aspects. Concerning the affective relationships and their transformations in the contemporary world, the author Bauman (2011) consolidated the research with his liquid approach. The affective relations studied through their new configuration grounded in the use of technological devices that build what Santaella (2003) calls cyberculture. The methodological procedures looked to engage with anthropology in what regards the field research, subsidized by an autoetnographic bias discussed from the authors Fortin (2009) and Versiani (2002). In this context, the performances Estás Rochas, Excesso, Pedras e Dores, Fios Condutores, Quando começa uma Performance?, and Cama de estar were created, which the creation processes are exposed throughout the dissertative text. Thus, a path was built to question the chosen issue through a poetic composed by a series of performances that encompass the social and cultural modifications that the heterosexual affective human relations are suffering in the last decades.